Salicylanilide ester prodrugs as potential antimicrobial agents--a review - Krátký, Martin; Vinsová, Jarmila (Current pharmaceutical design, 2011)
Salicylanilides have been a subject of interest in medicinal chemistry as a group with a wide range of biological activities. The antibacterial (including antimycobacterial) and antifungal activities have come to be viewed as very significant. The synthesis of new prodrugs to counter a number of problematic properties of salicylanilides is a current trend. This article brings together the known basic facts about these prodrugs, particularly about the different mechanisms of the antimicrobial action of salicylanilides, including salicylanilide toxicity and undesired effects. The largest part of this group consists of antimicrobial salicylanilide esters with different organic acids, e.g. acetates, carbamates, esters with N-protected amino acids, and mutual antibacterial compounds with known antibacterial agents (β-lactames and linezolid), with the activity and structure-activity relationships of these compounds being of particular interest. This review summarizes the activity of salicylanilides as potential virulence inhibitors attributable to a blockade of the type III secretion pathway. Many salicylanilide ester derivatives have been demonstrated an effective and promising treatment against pathogenic fungi and bacteria (especially against Gram-positive, tuberculous and atypical mycobacterial strains), including strains such as methicillin-resistant Staphylococcus aureus and isoniazid-resistant mycobacteria which are resistant to one or more clinically used drugs.
Keywords: Humans; Structure-Activity Relationship; vztahy mezi strukturou a aktivitou; antifungální látky; Prodrugs; lidé; antibakteriální látky; zvířata; molekulární struktura; Drug Design; Molecular Structure; Esters; Anti-Bacterial Agents; Antifungal Agents; racionální návrh léčiv; prekurzory léčiv; salicylanilidy; Salicylanilides; Animals; estery